Optimal manufacturing and remanufacturing capacities of systems with reverse logistics and deterministic uniform demand - Ernest Benedito; Albert Corominas (Journal of Industrial Engineering and Management (JIEM), 2010)
Using reverse logistics in production systems can help to reduce costs. However, it can also mean introducing a source of uncertainty in the system behavior. In this study we present a method for calculating the optimal manufacturing and remanufacturing capacities of a system with reverse logistics and steady demand taking into account the random behavior of the quantity, quality and timing of units that are collected thru the reverse logistics system. The collected units are remanufactured or disposed of. We also provide an example to illustrate the method.
Keywords: 650; reverse logistics; remanufacturing; capacity planning